Profile of Candi Muaro Jambi Tour Guide Towards International Destination - Desti Angraini (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2021)
This research aims to know the readiness of the tour guide in Candi Muaro Jambi toward sinternational destination. To know the readiness of the tour guide, this research will specifically explore the profile of the tour guide, especially with regards to English proficiency. To determine the profile of tour guide, the research method used in this study was qualitative descriptive approach. In this research can be concluded a few things: (1) Profile tour guide of Candi Muaro Jambi related English ability still very minimal, (2) Tour Guide of Candi Muaro Jambi has positive mental attitude and a good ability to know the history of tourist attractions. There has been no improvement of English done by the Tour Guide itself, because there is no well-organized supervision of the institution.